Altered Parietal Activation during Non-symbolic Number Comparison in Children with Prenatal Alcohol Exposure - Woods, Keri J.; Jacobson, Sandra W.; Molteno, Christopher D.; Jacobson, Joseph L.; Meintjes, Ernesta M. (Frontiers in Human Neuroscience, 2018)
Number processing is a cognitive domain particularly sensitive to prenatal alcohol exposure, which relies on intact parietal functioning. Alcohol-related alterations in brain activation have been found in the parietal lobe during symbolic number processing. However, the effects of prenatal alcohol exposure on the neural correlates of nonsymbolic number comparison and the numerical distance effect have not been investigated. Using functional magnetic resonance imaging (fMRI), we examined differences in brain activation associated with prenatal alcohol exposure in five parietal regions involved in number processing during a nonsymbolic number comparison task with varying degrees of difficulty. fMRI results are presented for 27 Cape Coloured children (6 fetal alcohol syndome (FAS)/partial FAS, 5 heavily exposed nonsydromal, 16 controls; mean age ± SD = 11.7 ± 1.1 years). Fetal alcohol exposure was assessed by interviewing mothers using a timeline follow-back approach. Separate subject analyses were performed in each of five regions of interest, bilateral horizontal intraparietal sulci (IPS), bilateral posterior superior parietal lobules (PSPL), and left angular gyrus (lAG), using the general linear model with predictors for number comparison and difficulty level. Mean percent signal change for each predictor was extracted for each subject for each region to examine group differences and associations with continuous measures of alcohol exposure. Although groups did not differ in performance, controls activated the right (r) PSPL more during nonsymbolic number comparison than exposed children, but this was not significant after controlling for maternal smoking, and the rIPS more than children with fetal alcohol syndrome (FAS) or partial FAS. More heavily exposed children recruited the lAG to a greater extent as task difficulty increased, possibly to compensate, in part, for impairments in function in the PSPL and IPS. Notably, in nonsyndromal heavily exposed children activation was impaired in the rPSPL, but spared in the rIPS. These results extend previous findings of poor rIPS recruitment during symbolic number processing in FASD, indicating that mental representation of relative quantity is affected by prenatal alcohol exposure for both symbolic and nonsymbolic representations of quantity.